2018
DOI: 10.3390/molecules23051104
|View full text |Cite
|
Sign up to set email alerts
|

Various Physiological Response to Graphene Oxide and Amine-Functionalized Graphene Oxide in Wheat (Triticum aestivum)

Abstract: An increasing number of investigations have been performed on the phytotoxicity of carbon-based nanomaterials duo to their extensive use in various fields. In the present study, we investigated the phytotoxicity of unfunctionalized graphene oxide (GO) and amine-functionalized graphene oxide (G-NH2) on wheat (Triticum aestivum) in the concentration range from 125 to 2000 μg/mL after 9 days of hydroponic culture. Our results found that the incubation with both nanomaterials did not affect the final seed germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 55 publications
4
20
0
Order By: Relevance
“…Studies on herbaceous plants have shown that graphene treatment can cause damage to the cell membrane [ 34 , 35 ]. The transmission electron microscopy images showed clear evidence of damage to the cell structure in the graphene treatment group relative to the CK ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on herbaceous plants have shown that graphene treatment can cause damage to the cell membrane [ 34 , 35 ]. The transmission electron microscopy images showed clear evidence of damage to the cell structure in the graphene treatment group relative to the CK ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…During the comparison of the effects of GO and amine-modified graphene (G-NH 2 ) it was found that at high concentrations (500, 100 or 2000 mg L −1 ), GO inhibited wheat germination and seedling growth, while the same doses of G-NH 2 exerted positive effects. The electrolite leakage of roots was increased by GO exposure supporting the toxic nature of this nanomaterial type [ 96 ]. According to Vochita et al [ 97 ], wheat seed germination was inhibited by a high dosage of GO (2000 mg L −1 ) and a slight reduction in root elongation was also observable at this concentration.…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…Graphene can be transferred from wheat roots to shoots and enter the cytoplasm and chloroplasts (Hu et al, 2014c); however, GO accumulation was not observed in the root cells of wheat (Chen et al, 2018a). Furthermore, GO did not accumulate in the seedlings of spinach and chive from if their seeds were treated with 50 mg/L GO (He et al, 2018).…”
Section: Phytotoxicity Of Gfnsmentioning
confidence: 99%
“…Compared to graphene and GO, hydrated graphene ribbon (HGR) not only promoted the germination rate of aged seed, but also increased root differentiation; the disordered layer structures of HGR played a key role in this process (Hu and Zhou, 2014). The observations of Chen et al (2018a) showed that GO induced obvious toxic symptoms in wheat, while amine-functionalized GO was non-toxic and enhanced plant growth. They inferred that the introduction of amines could decrease the surface electrical resistivity of GO, creating higher electronic conductivity, and activating bioactivity in plant cells.…”
Section: Factormentioning
confidence: 99%